PBAT film capable of adhering water-based ink and preparation method thereof
Patent Information
- Application Number
- CN202311552102.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-21
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-11-21
AI Technical Summary
[0004]中国专利CN113400793A公开了一种可降解塑料包装袋绿色印刷工艺,用以解决现有设备在使用滚筒丝网印刷时出现刮伤风险等印刷问题,以及印刷过程中出现的印刷残缺和造成印刷质量层次不齐的现象,但其改善以工艺为主,未涉及材料配方优化
[0032]使用本方案得到的可降解塑料的油墨附着性能好,所制备的包装袋或购物袋油墨附着力高,印刷牢固、客户使用感受优。
Smart Images

Figure BDA0004559852000000091 
Figure BDA0004559852000000101
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biodegradable materials, and in particular relates to a PBAT film that can be coated with water-based inks and its preparation method. Background Technology
[0002] With the development of the national economy, the large-scale use and waste of plastics has brought many problems to the global environment and resources. Packaging films are one of the main sources of plastic waste. With the implementation of plastic bans, developing biodegradable polymer materials, especially biodegradable films, is an effective way to fundamentally solve the problems of plastic waste pollution and energy. Biodegradable packaging films have the advantages of being green and environmentally friendly and having wide applications, making them one of the most promising research directions for solving global environmental and resource problems. However, the preparation of packaging bags or shopping bags from biodegradable film materials suffers from problems such as poor ink adhesion, leading to poor printing and a poor user experience. Therefore, it is urgent to improve the ink adhesion performance of biodegradable plastics to expand their application range.
[0003] Polybutylene terephthalate (PBAT) is a fully biodegradable polyester material that can be metabolized and broken down by microorganisms, ultimately becoming carbon dioxide and water. PBAT has good ductility and elongation at break, and its film also possesses a certain degree of strength. During printing and lamination processes, the surface tension of the plastic film must be greater than the surface tension (surface free energy) of the ink and adhesive (glue) to ensure good adhesion (firmness) of the ink or adhesive to the plastic film. Because biodegradable PBAT films have a smooth surface, their surface adhesion is relatively poor, leading to poor ink adhesion, poor packaging appearance, and a bad user experience. Therefore, developing a biodegradable PBAT film that can efficiently adhere to water-based inks and its preparation method is of great significance.
[0004] Chinese patent CN113400793A discloses a green printing process for biodegradable plastic packaging bags, which aims to solve printing problems such as the risk of scratches when using existing equipment for roller screen printing, as well as printing defects and inconsistent printing quality during the printing process. However, its improvement is mainly based on the process and does not involve the optimization of material formulation.
[0005] Chinese patent CN113121964A discloses an environmentally friendly biodegradable packaging bag and its preparation method, but it mainly meets the mechanical performance requirements of fully biodegradable mulch film products and does not aim to improve the ink printing adhesion performance of PBAT film.
[0006] Currently, there is a lack of systematic research on improving the adhesion of water-based inks to biodegradable films. Due to insufficient ink adhesion, most current ink printing processes for biodegradable packaging bags involve corona treatment of the film surface to improve ink adhesion. This corona treatment process primarily generates gases such as ozone, nitrogen dioxide, and nitric oxide. Ozone has a pungent odor and can be harmful to human health at concentrations exceeding a certain level. Furthermore, corona treatment machines generate noise pollution. Therefore, developing biodegradable PBAT films that can adhere to water-based inks without requiring a corona printing process has significant practical and economic value. Summary of the Invention
[0007] To address the above technical problems, this invention provides a novel adhesive water-based ink PBAT film and its preparation method. By improving the PBAT film formulation, the surface polarity, surface roughness, and oil absorption of the film are increased, thereby improving the adhesion of water-based inks to the biodegradable film.
[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0009] A PBAT film capable of adhering to water-based inks comprises the following raw materials in weight fractions:
[0010] S1, PBAT resin 75.4-92.5%, preferably 82.4-92.5%;
[0011] S2, PLA resin 5-20%, preferably 5-15%;
[0012] S3, rosin 0.5-2.5%, preferably 1-2%;
[0013] S4, maleic anhydride 0.3-1%, preferably 0.6-1%;
[0014] S5, peroxide 0.1-1%, preferably 0.4-0.5%;
[0015] S6, slip agent 0.2-1%, preferably 0.2-0.4%;
[0016] S7, chain extender 0.1-0.5%, preferably 0.2-0.4%;
[0017] The total weight of the above raw materials is taken as 100%.
[0018] In a specific embodiment of the present invention, the PBAT resin refers to a blown film grade resin with a melt flow index (MFR) of 2-10 g / 10 min at 190°C and a load of 2.16 kg.
[0019] In one specific embodiment of the present invention, the PLA resin refers to a resin with a melt flow index (MFR) of 2-20 g / 10 min.
[0020] In one specific embodiment of the present invention, the peroxide is selected from one or more of dicumyl peroxide and bis-tert-butylperoxide.
[0021] In one specific embodiment of the present invention, the slip agent is one or more selected from erucamide, stearamide, behenamide, and oleamide. The slip agent gradually precipitates onto the film surface, effectively reducing the coefficient of friction between films and improving the slip properties of the film.
[0022] In one specific embodiment of the present invention, the chain extender is one or more of styrene-methacrylate-glycidyl methacrylate copolymer and isocyanate, preferably styrene-methacrylate-glycidyl methacrylate copolymer with a functionality of 9.
[0023] Maleic anhydride is a polar compound containing multiple functional groups, and its anhydride groups can react with functional groups such as hydroxyl, carboxyl, and amine groups. PLA and PBAT are also polyester materials, and their molecular chains contain carboxyl and hydroxyl groups at the ends, which can react with maleic anhydride during processing and modification. Introducing highly polar reactive groups through maleic anhydride gives the material high polarity, thereby improving the ink adhesion of the film material. Introducing rosin components into PBAT films, and considering that maleic anhydride can react simultaneously with rosin and PLA, acting as a "bridge" between rosin and PLA / PBAT, increases the compatibility of rosin with PBAT / PLA. Since inks contain components similar to or the same as rosin, according to the principle of like compatibility, the printability of inks on PBAT films can be significantly improved, increasing ink adhesion.
[0024] The present invention also provides a method for preparing the PBAT thin film, comprising the following steps:
[0025] A. PLA resin, rosin, maleic anhydride, and peroxide are added to an extruder for melt extrusion granulation. After water cooling and pelletizing, granules 1 are obtained.
[0026] Preferably, in step A, the above-mentioned raw materials are added through the main feed port. The extruder is a twin-screw extruder with an extruder speed of 300-600 rpm and an extrusion temperature of 150-220℃, preferably 180-190℃.
[0027] B. Add the above-mentioned particles 1, PBAT resin, chain extender, and slip agent to an extruder for melt extrusion granulation. After water cooling and pelletizing, PBAT film granules that can be coated with water-based inks are obtained.
[0028] In step B, the extruder is a twin-screw extruder with a rotation speed of 300-600 rpm and a reaction temperature of 150-210℃, preferably 180-190℃.
[0029] C. Further process PBAT granules to obtain PBAT composite films.
[0030] Preferably, a blown film extrusion machine is used to prepare the PBAT composite film, with the screw temperature of the extrusion machine being 130-180℃, preferably 140-160℃, and the rotation speed being 5-30Hz, preferably 10-20Hz.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] The biodegradable plastics obtained using this method have good ink adhesion properties, resulting in packaging bags or shopping bags with high ink adhesion, strong printing, and a superior user experience. Detailed Implementation
[0033] The embodiments described in this invention are merely illustrative and do not limit the scope of the invention.
[0034] The main raw materials in this example are sourced from the following sources:
[0035] PBAT: TH 801T, melt index 3-5 g / 10 min (190℃, 2.16 kg), weight average molecular weight 100,000, melting point 120℃, Lanshan Tunhe
[0036] PLA: LX175, melt index 3-5 g / 10 min (190℃, 2.16 kg), weight-average molecular weight 170,000, melting point 155℃, Total Kronen
[0037] Rosin: AT01, softening point (ring and ball method) 70-80℃, Shenzhen Yoshida Chemical Co., Ltd.
[0038] Maleic anhydride: purity ≥99.5%, melting point 51-56℃, Qixiang Tengda Chemical Co., Ltd.
[0039] Dicumyl peroxide: Purity ≥ 99.5%, Melting point 41-42℃, Guangzhou Sanming Chemical Co., Ltd.
[0040] Di-tert-butylperoxyisopropylbenzene: purity ≥99.5%, melting point 44-48℃, produced by Sinopec Shanghai Gaoqiao Petrochemical Co., Ltd.
[0041] Erucamide: Croda Chemicals (Shanghai) Co., Ltd.
[0042] Oleamide: Croda Chemicals (Shanghai) Co., Ltd.
[0043] Ethylene bis-stearamide: Croda Chemicals (Shanghai) Co., Ltd.
[0044] Behenamide: Croda Chemicals (Shanghai) Co., Ltd.
[0045] Chain extender: Styrene-methacrylate-glycidyl methacrylate copolymer: ADR4468, BASF
[0046] Specific performance testing methods:
[0047] The mechanical properties of the specimens were tested using a ZWICK Z0.5TH single-column universal testing machine according to the national standard GB / T 1040.3-2006. The gauge length was 50 mm, the tensile speed was 500 mm / min, the sample width was 15 mm, the length was 150 mm, the test temperature was 23℃, and the humidity was 50%.
[0048] The ink adhesion fastness test was conducted according to the standards GB / T 38082-2019 Biodegradable Plastic Shopping Bags and GB 13217.7-2009 Test Method for Adhesion Fastness of Liquid Ink. The test principle employed was the tape peeling method to determine the peeling rate of film ink. A 3M 681 type tape (25mm wide) was applied to the printed surface of the sample, ensuring it was flat and 175mm long. It was folded 180° at 75mm, resulting in a tape adhesion area of 2500mm². 2 Roll the adhesive tape back and forth three times with a 1kg roller at the pasting area. Check for air bubbles in the pasted area. If there are air bubbles, remove them with a suitable tool and roll the tape again with the roller. After waiting for 5 minutes, apply force at a 45° angle to the printed surface and peel it off quickly by hand, keeping the time within 2 seconds.
[0049] If the peeling is a complete detachment: After peeling, use a ruler with a 1mm graduation or an area measuring card to measure the peeled area and the residual area of the printing ink, and calculate the printing ink peeling rate according to the following formula. Use 3 samples, take the average value, and round the result to 1%.
[0050] δ=(S b / S t )×100%
[0051] Where: δ—printing peel rate; S b —Peeling area; S t —Total area covered by tape;
[0052] If the peeling is shallow and of varying degrees: the area card cannot effectively measure the peeling area, and the peeling rate needs to be expressed in other ways; in this case, the color of the peeled printed material and the difference in the degree of peeling are recorded by recording the width of the obvious peeling point of different printed colors in the 10cm*2.5cm tape area for quantitative comparison, and the results are presented with feedback photos to assist in the presentation;
[0053] The surface tension of the film is tested using a Cuiyuan dyne pen with a dyne value ranging from 26 to 46. Holding the dyne pen perpendicular to the film plane and applying appropriate pressure, draw a line on the film surface. If the line is evenly distributed without any beads, it indicates that the surface tension of the film is higher than the index marked on the dyne pen, indicating good printing results. If the line slowly shrinks, it indicates that the surface tension of the film is slightly lower than the index marked on the dyne pen.
[0054]
Example 1
[0055] Prepare a PBAT film with high adhesion to water-based inks according to the following steps:
[0056] 1) 500g of PLA resin LX175, 100g of rosin AT01, 40g of maleic anhydride, and 50g of dicumyl peroxide were fed into a twin-screw extruder through the main feed port. The speed was 300 rpm and the extrusion temperature was 180℃. The extrusion was carried out by melt extrusion granulation. After water cooling and pelletizing, maleic anhydride grafts were obtained.
[0057] 2) The above mixture, along with 9250g of PBAT resin TH801T, 40g of slip agent erucamide, and 20g of chain extender, are fed into a twin-screw extruder through the main feed port at a speed of 500 rpm and a reaction temperature of 200℃. The mixture is then melt-extruded and granulated. After water cooling and pelletizing, modified granules for blown film production are obtained.
[0058] 3) Add the modified PBAT granules into a blown film machine and further process them to obtain a PBAT composite film.
[0059]
Example 2
[0060] Prepare a PBAT film with high adhesion to water-based inks according to the following steps:
[0061] 1) 1000g of PLA resin LX175, 250g of rosin AT01, 60g of maleic anhydride, and 10g of dicumyl peroxide were fed into a twin-screw extruder through the main feed port. The speed was 500 rpm and the extrusion temperature was 200℃. The extrusion was carried out by melt extrusion granulation. After water cooling and pelletizing, maleic anhydride grafts were obtained.
[0062] 2) The above mixture, along with 8650g of PBAT resin TH801T, 20g of slip agent erucamide, and 10g of chain extender, are fed into a twin-screw extruder through the main feed port at a speed of 300 rpm and a reaction temperature of 190℃. The mixture is then melt-extruded and granulated. After water cooling and pelletizing, modified granules for blown film are obtained.
[0063] 3) Add the modified PBAT granules into a blown film machine and further process them to obtain a PBAT composite film.
[0064]
Example 3
[0065] Prepare a PBAT film with high adhesion to water-based inks according to the following steps:
[0066] 1) 1500g of PLA resin LX175, 50g of rosin AT01, 30g of maleic anhydride, and 100g of dicumyl peroxide were fed into a twin-screw extruder through the main feed port at a speed of 300 rpm and an extrusion temperature of 190℃. The mixture was melt-extruded and granulated. After water cooling and pelletizing, maleic anhydride grafts were obtained.
[0067] 2) The above mixture, along with 8190g of PBAT resin TH801T, 100g of slip agent erucamide, and 30g of chain extender, are fed into a twin-screw extruder through the main feed port at a speed of 400 rpm and a reaction temperature of 210℃. The mixture is then melt-extruded and granulated. After water cooling and pelletizing, modified granules for blown film are obtained.
[0068] 3) Add PBAT modified granules into a blown film machine for further processing to obtain PBAT composite films.
[0069]
Example 4
[0070] Prepare a PBAT film with high adhesion to water-based inks according to the following steps:
[0071] 1) 2000g of PLA resin LX175, 200g of rosin AT01, 80g of maleic anhydride, and 40g of di-tert-butylperoxyisopropylbenzene were fed into a twin-screw extruder through the main feed port at a speed of 400 rpm and an extrusion temperature of 220℃. The mixture was melt-extruded and granulated. After water cooling and pelletizing, maleic anhydride grafts were obtained.
[0072] 2) The above mixture, along with 7550g of PBAT resin TH801T, 80g of slip agent erucamide, and 50g of chain extender, are fed into a twin-screw extruder through the main feed port at a speed of 350 rpm and a reaction temperature of 180℃. The mixture is then melt-extruded and granulated. After water cooling and pelletizing, modified granules for blown film production are obtained.
[0073] 3) Add the modified PBAT granules into a blown film machine and further process them to obtain a PBAT composite film.
[0074]
Example 5
[0075] Prepare a PBAT film with high adhesion to water-based inks according to the following steps:
[0076] 1) 1000g of PLA resin LX175, 150g of rosin AT01, 100g of maleic anhydride, and 50g of dicumyl peroxide were fed into a twin-screw extruder through the main feed port. The speed was 600 rpm and the extrusion temperature was 210℃. The extrusion was carried out by melt extrusion granulation. After water cooling and pelletizing, maleic anhydride grafts were obtained.
[0077] 2) The above mixture, along with 8600g of PBAT resin TH801T, 60g of slip agent erucamide, and 40g of chain extender, are fed into a twin-screw extruder through the main feed port at a speed of 600 rpm and a reaction temperature of 220°C. The mixture is then melt-extruded and granulated. After water cooling and pelletizing, modified granules for blown film production are obtained.
[0078] 3) Add the modified PBAT granules into a blown film machine and further process them to obtain a PBAT composite film.
[0079] Comparative Example 1
[0080] Replace 100g of rosin AT01 in Example 1 with 100g of PLA resin LX175, while keeping all other conditions unchanged.
[0081] Comparative Example 2
[0082] Maleic anhydride and dicumyl peroxide were not added in this comparative example, and other conditions were the same as in Example 2.
[0083] Comparative Example 3
[0084] The main difference between this comparative example and Example 2 is that 250g of rosin AT01, 60g of maleic anhydride, and 50g of dicumyl peroxide were all replaced with an equal mass of PBAT resin TH801T, while all other conditions remained unchanged.
[0085] Comparative Example 4
[0086] In Example 2, 60g of maleic anhydride was replaced with maleic anhydride graft (PLA-g-MAH), while all other conditions remained unchanged.
[0087] The modified materials prepared in Examples 1-5 and Comparative Examples 1-4 were blown into films with a thickness of 30 μm. After standing for 24 h, relevant tests were performed, as shown in Table 1.
[0088] Table 1. Characterization of the effects of PBAT-modified films prepared in the examples and comparative examples.
[0089]
[0090]
[0091] As can be seen from Comparative Examples 1-4 and Example 4, compared with the absence of maleic anhydride and rosin, the ink of the present invention has significantly improved adhesion performance and mechanical properties, thus meeting the requirements of downstream applications.
[0092] The above description is only a preferred embodiment of the present invention. It should be noted that those skilled in the art can make several improvements and additions without departing from the method of the present invention, and these improvements and additions should also be considered within the scope of protection of the present invention.
Claims
1. A PBAT film capable of adhering to water-based inks, characterized in that, The raw materials include the following mass fractions: S1, PBAT resin 75.4-92.5%; S2, PLA resin 5-20%; S3, rosin 0.5-2.5%; S4, maleic anhydride 0.3-1%; S5, peroxide 0.1-1%; S6, slip agent 0.2-1%; S7, chain extender 0.1-0.5%; Based on the total mass of the above raw materials being 100%; The method for preparing the PBAT thin film includes the following steps: A. PLA resin, rosin, maleic anhydride, and peroxide are added to an extruder for melt extrusion granulation. After water cooling and pelletizing, granules 1 are obtained. B. Add the above-mentioned particles 1, PBAT resin, chain extender, and slip agent to an extruder, perform melt extrusion granulation, and after water cooling and pelletizing, obtain PBAT film granules that can be adhered to water-based inks. C. Further process PBAT granules to obtain PBAT composite films.
2. The PBAT film according to claim 1, characterized in that, The mass fraction of each raw material is as follows: S1 and PBAT resins: 82.4-92.5%; S2, PLA resin 5-15%; S3, rosin 1-2%; S4, maleic anhydride 0.6-1%; S5, peroxide 0.4-0.5%; S6, slip agent 0.2-0.4%; S7, chain extender 0.2-0.4%; Based on the total mass of the above raw materials as 100%.
3. The PBAT film according to claim 1, characterized in that, The PBAT resin is a resin with a melt index of 2-10 g / 10 min at 190°C and a load of 2.16 kg.
4. The PBAT film according to claim 1, characterized in that, The PLA resin is a resin with a melt index of 2-20 g / 10 min at 190°C and a load of 2.16 kg.
5. The PBAT film according to claim 1, characterized in that, The peroxide is selected from one or more of dicumyl peroxide and bis-tert-butylperoxyisopropylbenzene.
6. The PBAT film according to claim 1, characterized in that, The slip agent is one or more of erucamide, stearamide, behenamide, and oleamide.
7. The PBAT film according to claim 1, characterized in that, The chain extender is one or more of styrene-methacrylate-glycidyl methacrylate copolymer and isocyanate.
8. The PBAT film according to claim 7, characterized in that, The chain extender is a styrene-methacrylate-glycidyl methacrylate copolymer with a functionality of 9.
9. The PBAT film according to claim 1, characterized in that, In step A, the above raw materials are added through the main feed port. The extruder is a twin-screw extruder with an extruder speed of 300-600 rpm and an extrusion temperature of 150-220℃.
10. The PBAT film according to claim 9, characterized in that, In step A, the extrusion temperature is 180-190℃.
11. The PBAT film according to claim 1, characterized in that, In step B, the extruder is a twin-screw extruder with a rotation speed of 300-600 rpm and a reaction temperature of 150-210℃.
12. The PBAT film according to claim 11, characterized in that, In step B, the reaction temperature is 180-190℃.
13. The PBAT film according to claim 1, characterized in that, PBAT composite films were prepared using a blown film extrusion machine with a screw temperature of 130-180℃ and a rotation speed of 5-30Hz.
14. The PBAT film according to claim 13, characterized in that, PBAT composite films were prepared using a blown film extrusion machine with a screw temperature of 140-160℃ and a rotation speed of 10-20Hz.
Citation Information
Patent Citations
Environment-friendly degradable packaging bag and preparation method thereof
CN113121964A
Degradable plastic packaging bag green printing process
CN113400793A
Starch modified PBAT / PLA biodegradable plastic film and preparation method thereof
CN113861635A
Composite material for biodegradable film rapidly and firmly printed by water-based ink and preparation method of composite material
CN116987369A